Mineral Compositions and Grain Sizes of Beach Sediments in Northern Vietnam - Thi Chien, Hoang; Dac Ve, Nguyen; Ngoc Nam, Nguyen; Thi Bich Thuy, Lai; Thi Mai Luu, Nguyen; Thi Thanh Loan, Bui; Hoai Nhon, Dang (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2DO - 10.25073/2588-1094/vnuees.5293, 2025)
Abstract: Forty three surface samples from the beaches of northern Vietnam from Quang Ninh to Thua Thien Hue were sampled in July 2024 for grain size and mineralogy analysis. We aim to assess the dynamic conditions and mineral origins of beach sediments. Three types of sediments were distributed on the beach: coarse sand, medium sand, and fine sand. Coarse sand was well sorted and symmetrically skewed. Medium sand was very well to moderately sorted and fine to coarsely skewed. Fine sand was very well to moderately well sorted and fine to coarsely skewed. Mineral contents including quartz, illite, feldspar, kaolinite, goethite, chlorite, calcite, amphibole, and gibbsite were 80.3%, 5.2%, 3.1%, 2.3%, 2.0%, 1.8%, 1.1%, 0.9%, and 0.1%, respectively. The mineral origins were from the mainland, characterized by quartz, feldspar, and amphibole; minerals as illite, chlorite, kaolinite, and goethite were products from chemical weathering of feldspar and amphibole; calcite from biological shells. Beach sediments were divided into three groups, characterized by particle size and quartz (lowest in group 1 and highest in group 3).